2019
DOI: 10.1093/jas/skz052
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dietary standardized ileal digestible lysine and crude protein concentration for growth and carcass performance in finishing pigs weighing greater than 100 kg1,2

Abstract: Three experiments were conducted to determine the optimal dietary standardized ileal digestible (SID) lysine and CP concentrations for finishing pigs over 100 kg BW. In Exp. 1, 253 pigs (DNA 600 × 241, initially 102.0 kg) were used in a 23-d trial with 7 to 8 pigs per pen and 8 pens per treatment. Dietary treatments contained 4 SID lysine concentrations (0.45, 0.55, 0.65, or 0.75%). To formulate the experimental diets, a corn-soybean meal diet with 0.45% SID lysine was formulated without L-lysine HCl. Then, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
1
17
2
Order By: Relevance
“…On average, control pigs consumed approximately 18–20 g/d SID Lys where pigs fed 0.18% SID Lys diets consumed approximately 10–12 g/d. Similarly, Soto et al (2019) reported a decrease in ADG and G:F as SID Lys intake per day decreased in 100- to 135-kg pigs, but the magnitude of reduction was less than what we observed in our experiments with severely deficient Lys diets. Goncalves et al (2017) reported that the optimal performance for ADG and G:F of 100- to 135-kg pigs was associated with a SID Lys intake per day of 19.5 and 19.7 g/d, respectively.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…On average, control pigs consumed approximately 18–20 g/d SID Lys where pigs fed 0.18% SID Lys diets consumed approximately 10–12 g/d. Similarly, Soto et al (2019) reported a decrease in ADG and G:F as SID Lys intake per day decreased in 100- to 135-kg pigs, but the magnitude of reduction was less than what we observed in our experiments with severely deficient Lys diets. Goncalves et al (2017) reported that the optimal performance for ADG and G:F of 100- to 135-kg pigs was associated with a SID Lys intake per day of 19.5 and 19.7 g/d, respectively.…”
Section: Discussioncontrasting
confidence: 57%
“…The NRC (2012) SID Lys requirement estimate is 0.73% for 75- to 100-kg pigs and 0.61% for 100- to 135-kg pigs. Soto et al (2019) reported that the predicted maximum ADG and G:F for pigs beyond 100-kg BW was achieved at 0.62% and 0.63% SID Lys, respectively. Distinct from regular Lys titration studies, we used diets (0.50%-Lys and 0.18%-Lys diet) that were severely deficient in Lys and other AAs for this weight range to evaluate the effects on growth performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of feed consumption and associated growth rate may be an important source of variation in estimated SID Lys requirements among experiments. Research conducted with 112–136 kg pigs in a university setting, reported an average feed intake of 3.1 kg ( Soto et al, 2019 ). Conversely, research conducted in a commercial environment reported an average feed intake of 2.6 kg for 102–120 kg pigs ( Main et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the variation in the response in PD to Lys and Thr observed was large, with Lys and Thr intake explaining only 11% (R 2 = 0.11) of the variation observed in PD. This large variation in growth performance is often observed in titration trials [11,18,19]. Due to the large data variation and presence of outliers, a more robust adjustment based on the LOESS procedure was adopted.…”
Section: The Simultaneous Determination Of Two Aa Requirementsmentioning
confidence: 99%